Functional development of swallowing in ICU patients with COVID-19 - Santilli, Maíra (2020)
Purpose: to describe de functional developement of swallowing in Intensive Care Unit (ICU) patients with COVID-19, who were submitted to a swallowing intervention. Method: participants of the study were 77 patients (both gender, mean age 53.4±15.9; score on the Glasgow Coma Scale ≥14 and stable respiratory condition). The functional scale of swallowing used for assessment was the American Speech-Language-Hearing Association National Outcome Measurement System (ASHA NOMS). Results: the results indicate that there was a significant recovery of the functional swallowing patterns when comparing the measurements pre and post swallowing intervention. Conclusion: 83% of the patients needed up to 3 swallowing interventions to recover a safe swallowing pattern.